What affects organization and collective action for managing resources? evidence from canal irrigation systems in India - Meinzen-Dick, Ruth S.; Raju, K. Vengama; Gulati, Ashok (International Food Policy Research Institute, 2000)
Policies of devolving management of resources from the state to user groups are premised upon the assumption that users will organize and take on the necessary management tasks. While experience has shown that in many places users do so and are very capable, expansion of co-management programs beyond initial pilot sites often shows that this does not happen everywhere. Yet, much is at stake in this, with more widespread adoption of irrigation management transfers and other forms of community-based resource management. It is therefore important to move beyond isolated case studies to comparative analysis of the conditions for collective action. This paper identifies factors affecting organization of water users’ associations, and collective action by farmers in major canal irrigation systems in India, based on quantitative and qualitative analysis of a stratified sample of 48 minors in four irrigation systems (two each in Rajasthan and Karnataka). Using key variables suggested by the theoretical and case study literature, the study first examines the conditions under which farmers are likely to form formal or informal associations at the level of the minor (serving several watercourses, and one or more villages). Results indicate that organizations are more likely to be formed in larger commands, closer to market towns, and in sites with religious centers and potential leadership from college graduates and influential persons, but head/tail location does not have a major effect. We then examine factors affecting two different forms of collective action related to irrigation systems: collective representation and maintenance of the minors. Lobbying activities are not more likely where there are organizations, but organizations do increase the likelihood of collective maintenance work. -- Author' Abstract